Cellular Peptide Hormone Synthesis and Secretory Pathways - Rehfeld, Jens F.; Bundgaard, Jens R.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The purpose of the present volume is to illustrate the modern biological concept of basic endocrinology in one single book. It first describes general issues such as maturation of secretory granules in the cells, the roles of the chaperonic granins, and cell-specific prohormone processing. Subsequently, the specific part of the book illustrates the new endocrine biology, using as examples a broad variety of individual peptide systems: ACTH, Neurotensin and Neuromedines, Natriuretic Peptides, Glucagon and Glucagon-like peptides, Somatostatin, Ghrelin, Gastrin and VIP (Vasoactive Intestinal Polypeptide).
VIP and PACAP -- Biosynthesis of Cardiac Natriuretic Peptides -- Chromogranins A and B and Secretogranin II as Prohormones for Regulatory Peptides from the Diffuse Neuroendocrine System -- Neurotensin and Neuromedin N Are Differentially Processed from a Common Precursor by Prohormone Convertases in Tissues and Cell Lines -- Ghrelin: From Gene to Physiological Function -- Somatostatin and Somatostatin Receptors -- ACTH: Cellular Peptide Hormone Synthesis and Secretory Pathways -- Maturation of Secretory Granules -- Cell-Specific Precursor Processing -- Posttranslational Processing of Progastrin -- Glucagon and Glucagon-Like Peptides 1 and 2.
Keywords: Life sciences; Biochemistry; Cytology; Life Sciences; Cell Biology; Biochemistry, general